2016
DOI: 10.1021/acsphotonics.6b00238
|View full text |Cite
|
Sign up to set email alerts
|

Intraband Hot-Electron Photoluminescence from Single Silver Nanorods

Abstract: We report the observation of the undocumented visible one-photon photoluminescence (PL) of single silver nanorods excited by 532 and 633 nm continuous wave lasers with single-nanoparticle spectroscopy. We attribute the PL of silver nanorods to the intraband transition excited hotelectron radiative decay. The PL of silver nanorods closely resembles the corresponding LSPR scattering spectrum, and both are dependent on their aspect ratio. The good correlation between the quantitative PL intensity and the absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 53 publications
4
84
0
Order By: Relevance
“…The selected area of the diffraction pattern (SEAD) of silver nanoprism (Figure 2(d)) indicated that the entire nanoparticle was a single crystalline structure [32][33][34]. The SEAD pattern was indexed according to planes of (111) and (200) reflection, and the crystal structure of silver is FCC on the basis of the d-spacing 2.4 and 2.04 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The selected area of the diffraction pattern (SEAD) of silver nanoprism (Figure 2(d)) indicated that the entire nanoparticle was a single crystalline structure [32][33][34]. The SEAD pattern was indexed according to planes of (111) and (200) reflection, and the crystal structure of silver is FCC on the basis of the d-spacing 2.4 and 2.04 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The results are summarized in Fig. 4a [25,[31][32][33], it generally involves electronic transitions within the sp-band, and therefore its spectrum depends sensitively on the temperature-dependent shape of the Fermi-Dirac distribution for the electron gas. Our measured incoherent emission spectra therefore undergo a significant transformation with increasing incident power.…”
Section: Discussionmentioning
confidence: 99%
“…1b , pathway (iv)). 47 Still plasmons play an important role, helping spatially localise electrons to surface areas around strong near-field regions or out-couple the radiation to the far-field. 44 Although the exact underlying mechanism of PL cannot be clarified further, the crucial role of LSPR in plasmonic nanostructure PL has now been recognised.…”
Section: Direct One-photon Photoluminescence Of Plasmonic Nanostructumentioning
confidence: 99%
“…Owing to the highly tuneable LSPR and the lightning rod effect, Au nanorods are the most widely studied nanoparticles, exhibiting the strong PL with a quantum efficiency of ∼10 –6 . 47 , 49 51 Therefore, when studying the PL of other nanoparticles, the observed PL intensity is often compared with that of Au nanorods to confirm signal enhancement. The aspect ratio of the rod or the excitation wavelength can also be adjusted to obtain a PL signal of the desired wavelength.…”
Section: Direct One-photon Photoluminescence Of Plasmonic Nanostructumentioning
confidence: 99%